1981
DOI: 10.1021/jo00338a031
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and stereoselective cleavage of epoxides with cyanoborohydride and boron trifluoride etherate

Abstract: hexen-l-yloxy)trimethylsilane, 6651-36-1; (1-cyclopenten-1-yloxy)trimethylsilane, 19980-43-9; trimethyl[ (1 -phenylethenyl)oxy ]silane, 13735-81-4; l,l'-[[l,2-bis(methylene)-l,2-ethanediyl]bis(oxy)bis(trimethyl)silane, 31411-71-9; trimethyl[ [(1 -phenylmethyl)etheny 1]oxy]silane, 59021-31-7; trimethyl[(1-methyl-2-phenylethenyl)oxy]silane, 43108-63-0; trimethyl[(6-methyl-l-cyclohexen-l-yl)oxy]silane, 19980-33-7; trimethyl[(2-methyl-l-cyclohexen-l-yl)oxy]silane,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…The 3-O-acetyl 24R,25-dihydroxy compound (3) thus obtained was isolated by silica gel column chromatography. 17) We were offered a sample of the (24R)-compound 3 (diastereomeric ratio, 24R : 24Sϭ96 : 4, as revealed by the signal intensity of 0.66 (24R) and 0.62 (24S) ppm of compound 4 in 1 H-NMR analysis [19][20][21] ) from the company and started the synthesis from the compound to obtain the key intemediate (13) via nine steps. Compound 13 was further converted into squalamine 1 in high yield by modified procedures of Kinney's method 9) via two further steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-O-acetyl 24R,25-dihydroxy compound (3) thus obtained was isolated by silica gel column chromatography. 17) We were offered a sample of the (24R)-compound 3 (diastereomeric ratio, 24R : 24Sϭ96 : 4, as revealed by the signal intensity of 0.66 (24R) and 0.62 (24S) ppm of compound 4 in 1 H-NMR analysis [19][20][21] ) from the company and started the synthesis from the compound to obtain the key intemediate (13) via nine steps. Compound 13 was further converted into squalamine 1 in high yield by modified procedures of Kinney's method 9) via two further steps.…”
Section: Resultsmentioning
confidence: 99%
“…Fujimoto and coworkers reported that the chemical shift of C-24 in 13 C-NMR spectra of steroids that bear epimeric 24-hydroxyl groups differs by about 0.4 ppm from the signals for (24R)-epimers appearing at higher field. [19][20][21] Peaks due to C-24 of the (24R)-O-benzoyl and (24S)-Obenzoyl compounds were observed at 79.4 ppm and 79.8 ppm, respectively. The 13 C-NMR spectra were measured by taking complete 13 C-NMR and inverse gated 13 C-NMR to obtain correct integration values of the peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Stereochemistry of the purified dihydroartemisinic alcohol was con-firmed to be (R) by comparison to published 1 H NMR results (25). Hyride attack to produce the (R) stereochemistry of the alcohol under these conditions necessitates that artemisinic-11S,12-epoxide be the substrate (36).…”
Section: Transition State Complex Structural Predictionsmentioning
confidence: 85%
“…Such phenomenon was further verified by the results obtained from the reaction of alkyl-substituted or alkyl-and phenylsubstituted more epoxides such as 2,3-epoxy-2-methylbutane and α-methylstyrene oxide: the products were 3-methyl-2-butanol and 2-phenyl-1-propanol, respectively, and the selectivity was also 100%. Such an anti-Markovnikov reductive ring-opening of epoxides has previously been achieved with BH 3 -THF in the presence of BF3, 5 NaBH3CN in the presence of BF3, 6 KPh3BH in the presence of Ph3B, 7 ( i PrO3)B, 8 Al-fluorodiisobutylalane (DIBAF), 9 and Al-methanesulfonyldiisobutylalane (DIBAO 3 SCH 3 ). 1 However, each reagent possesses its own limitations of the reduction, such as a relatively low regioselectivity require- ment for drastic reaction conditions, as undesirable rearrangement product, a relatively low chemoselectivity, etc.…”
Section: Resultsmentioning
confidence: 99%